The buzz about bees and poverty alleviation: Identifying drivers and barriers of beekeeping in sub-Saharan Africa - Amulen, Deborah R.; D'Haese, Marijke; Ahikiriza, Elizabeth; Agea, Jacob G.; Jacobs, Frans J.; de Graaf, Dirk C.; Smagghe, Guy; Cross, Paul (PLoS one, 2017)
The potential of beekeeping to mitigate the exposure of rural sub-Sahara African farmers to economic stochasticity has been widely promoted by an array of development agencies. Robust outcome indicators of the success of beekeeping to improve household well-being are unfortunately lacking. This study aimed to identify the key drivers and barriers of beekeeping adoption at the household level, and quantified the associated income contribution in three agro-ecological zones in Uganda. Beekeepers were generally the most economically disadvantaged people in the study areas and tended to adopt beekeeping following contact with non-government organisations and access to training. Whilst incomes were not statistically lower than their non-beekeeping counterparts; their mean household well-being scores were significantly lower than non-beekeeping households. The inability of beekeeping to significantly improve well-being status can in part be attributed to a lack of both training in bee husbandry and protective equipment provision such as suits, gloves and smokers. These are critical tools for beekeepers as they provide the necessary confidence to manage honey bees. Rather than focussing solely on the socio-economic conditions of farmers to effectively adopt beekeeping, future research should also attempt to evaluate the effectiveness of development agencies' provision to the beekeeping sector.
Keywords: bees; poverty alleviation; beekeeping; sub-Saharan Africa